The Development of Web-Based Maharah Kalam Teaching Materials: (Research at Dairobby Vocational High School) - Jamaludin, Agus; Syafei, Isop (IIUM Journal of Educational Studies, 2025)
The vision of Da’i Rabbi Vocational Islamic Senior High School integrates the Qur’an, Pancasila values, and technology through a holistic curriculum grounded in constructivism and multiple intelligences, intending to shape a well-balanced student character. The primary issue addressed in this study is the limited Arabic language proficiency among students at Da’i Rabbi Vocational Islamic Senior High School. This issue stems from low student motivation, the lack of suitable instructional materials tailored to the technological orientation of vocational school students, and the need for an interactive, practical, and contextual digital learning tool aligned with the developments of the digital age. The objective of this research is to explore the educational profile of Da’i Rabbi Vocational School, to design a web-based Arabic speaking skill module, and to assess its validity, practicality, and effectiveness. This study adopts the ADDIE instructional design model, which comprises five systematic phases: Analysis, Design, Development, Implementation, and Evaluation. Data were collected from key sources including students, a subject matter expert, and a media expert, using various data collection tools such as observation, interviews, and evaluative questionnaires. The findings revealed that the instructional approach at Da’i Rabbi Vocational School is learner-centered, project-based, specialization-oriented, and grounded in ethical values, with increasing student interest in technology-enhanced learning. Nevertheless, the need to strengthen Arabic speaking proficiency was evident. In response, a web-based instructional material was developed following the five ADDIE phases. The development process was successfully conducted. The results concluded that the developed material demonstrated high validity (“very valid”), strong practicality (“practical”), and significant effectiveness (“very high effect size”) in improving students’ Arabic speaking skills.